Diversifikasi pengolahan pepaya di Kabupaten Enrekang - Hartati Hartati; Halifah Pagarra; A. Mu’nisa (DEDIKASI, 2019)
Community service about papaya processing diversification has been carried out in Enrekang Regency. This activity was carried out to improve the knowledge and skills of the people in Enrekang district in processing papaya into products of economic value, namely jams papaya and shredded papaya. This activity is carried out in stages, namely the presentation of material, papaya fruit processing practices into jam and shredded, reflection and evaluation of activities. The results show that the community is able to process papaya into papaya jam products and shredded papaya, and produce products that have been packaged with labeling. This activity also received a very good response to the community. The results of this activity are expected to be developed into a home-based business to increase the income of housewives in Enrekang district.